A novel glycobiomarker, Wisteria floribunda agglutinin macrophage colony‐stimulating factor receptor, for predicting carcinogenesis of liver cirrhosis. Issue 6 (20th October 2015) - Iio, Etsuko; Ocho, Makoto; Togayachi, Akira; Nojima, Masanori; Kuno, Atsushi; Ikehara, Yuzuru; Hasegawa, Izumi; Yatsuhashi, Hiroshi; Yamasaki, Kazumi; Shimada, Noritomo; Ide, Tatsuya; Shinkai, Noboru; et al.
Abstract : Recently, we identified a novel liver fibrosis glycobiomarker, Wisteria floribunda agglutinin (WFA)‐reactive colony stimulating factor 1 receptor (WFA + ‐CSF1R), using a glycoproteomics‐based strategy. The aim of this study was to assess the value of measuring WFA + ‐CSF1R levels for the prognosis of carcinogenesis and outcome in liver cirrhosis (LC) patients with hepatitis C virus (HCV). WFA + ‐CSF1R and Total‐CSF1R levels were measured in serum samples from 214 consecutive HCV‐infected patients to evaluate their impact on carcinogenesis and the survival of LC patients. Serum WFA + ‐CSF1R levels were significantly higher in LC patients than chronic hepatitis (CH) patients ( p  < 0.001). The AUC of WFA + ‐CSF1R for predicting overall survival, calculated by time‐dependent ROC analysis, was 0.691 and the HR (per 1‐SD increase) was 1.80 (95% CI, 1.23–2.62, p  < 0.001). Furthermore, the survival rate of LC patients with high WFA + ‐CSF1R levels (≥310 ng/ml) was significantly worse than those with lower levels ( p  < 0.01). The AUC of WFA + /total‐CSF1R percentage (WFA + ‐CSF1R%) for predicting the cumulative carcinogenesis rate was 0.760, with an HR of 1.66 (95% CI 1.26–2.20, p  < 0.001). In fact, the carcinogenesis rate was significantly higher in LC patients with a high WFA + ‐CSF1R% (≥ 35%, p  = 0.006). Assessing serum levels of WFA + ‐CSF1R has diagnostic value for predicting carcinogenesis and the survival of LC patients. Abstract : What's new? To find better biomarkers of liver fibrosis the authors developed a novel assay to detect serum levels of Wisteria floribunda agglutinin (WFA)‐reactive colony‐stimulating factor 1 receptor (WFA + ‐CSF1R). CSF1R is a membrane glycoprotein associated with cell proliferation and found elevated in a variety of cancers. They report that in hepatitis C virus‐infected patients who developed liver cirrhosis, the survival rate of patients with high WFA + ‐CSF1R levels was significantly worse. Similarly, the carcinogenesis rate was higher in patients with high percentage of WFA + ‐CSF1R, suggesting that this glycobiomarker may have clinical applications beyond the mere evaluation of liver fibrosis.